Geographical and ecological analysis of dry mollusks in uzbekistan and adjacent regions - F. Gaibnazarova; Kh.Karimova; Z.Muhammadiyev (International Journal on Human-Computing Studies, 2021)
High abundance, wide distribution, large species diversity, low mobility and low ability to overcome geographical barriers, ease of material collection and sensitive reaction to changes of external environments make the group of terrestrial mollusk in this territory convenient object of biographical and environmental studies